IMMUNOLOGIC PARAMETERS OF LIQUOR AT THE FORMING OF EPIDURAL FIBROSIS IN LUMBAR SEGMENT OF SPINE - P. G. Gruzin (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
Concentrations and composition of acute-phase proteins in liquor were studied by method of ultraviolet absorption. spectroscopy in 15 patients without neurological diseases and. in 25 patients with syndrome of spinal canal structures compression. The role of acute-phase proteins of liquor in forming of epidural fibrosis was determined. Significance of denaturated proteins of liquor in pathogenesis of syndrome of compression of lumbar segment of spine was revealed.